RITUAL CHENG BENG DALAM MASYARAKAT KHONGHUCU DAN KETERLIBATAN MASYARAKAT ISLAM DI KELURAHAN TEBING TINGGI - Soeyiwo Meliala, Mhd Bagoes (CV. Kalimasada Group, 2024)
This study discusses the Cheng Beng Ritual in the Confucian Society and the invention of the Islamic Society in Tebing Tinggi Village. Ritual is a habit of religious ceremonial procedures that are owned by various religions and have differences in each religion or tribe, in this discussion we take the Cheng Beng Ritual which uses the Theory of Religious Rituals from Emile Durkheim. In this study the authors used qualitative research methods by observing, documenting, and interviewing the research locations directly. Durkheim said in his book The Elementary from on the Agamauos life, which reviews social phenomena in depth, including the practice of religious rituals which Durkheim divides into two parts: 1. Negative ritual practices, which aim to form prohibitions in a religious ritual. 2. Positive ritual practices, aiming to manifest oneself with solemn faith. Durkeim also said that the rituals also make the relationship between families close again. Likewise with the cheng ben ritual which makes families gather to visit their ancestors. Meanwhile the Cheng Beng that occurred in the city of Tebing Tinggi did not only show harmonious relations in the Confucian society, but this Cheng Beng also became harmonious because the Islamic community of Tebing Tinggi Village participated in this Cheng beng event, there were several forms of harmony and involvement of the Islamic community in Cheng Beng, among others, assisting Cheng Beng ceremonies such as cleaning meals, giving circles to burn offering papers, selling around the tomb, joining the Cheng Beng YASOBAS Committee. With the aim of gaining profit and increasing the economic income of the Islamic community around the Chinese Cemetery and also for everyday life and making inter-religious relations harmonious.